My R-Pocket (Digital Receipt Mobile Application) - Rosdi Anuar, Nadia Asyiqin (IRC, 2019)
The development of My R-Pocket is one of the initiatives for retails industry. An important aspect of shopping is the receipt that is given to customers. The customer may find the paper receipt less than ideal for a number of reasons: it can be easily lost, damaged or destroyed. This could be a problem when the customer wishes to use the paper receipt to organize his personal finances or to exchange the item of purchase. If the receipt is damaged to a point where it’s longer valid, the customer may not be able to properly document or manage his accounting. Therefore, an improved system that keeps digital receipts of commercial transactions would be beneficial. The main goal of this project is to develop and implement a system of digital receipts for local transactions in commercial spaces, thus suppressing the need for paper receipts and reducing costs for business entities. This system will likely include the establishment of a connection between the mobile device of the customer and the fixed terminal in the store, and the transmission and storage of the receipt. Finally, this mobile application is uses the internet connectivity in order to regulate the works without manpower.